Cardiovascular Risk Factors in Chronic Inflammatory Rheumatic Diseases: Modern Assessment and Diagnosis - Rezu, Elena; Floria, Mariana; Grigoriu, Anca; I. Tamba, Bogdan; Rezus, Ciprian (Current Vascular Pharmacology, 2015)
The current view is that systemic inflammation, which is specific to all chronic inflammatory rheumatic diseases (CIRD), accelerates atherogenesis; this hypothesis is supported by the high cardiovascular (CV) morbidity and mortality rates and the high prevalence of all atherosclerosis stages and complications in CIRD patients. The assessment of traditional CV risk factors underestimates the actual risk in patients with CIRD. A comprehensive evaluation and follow-up of both traditional and non-traditional CV risk factors, as well as the correct classification of risk reduction categories are necessary. Imaging techniques (e.g. carotid intima-media thickness and flow-mediated vasodilation) can be used for the early diagnosis of endothelial dysfunction. Immunologic and metabolic markers (anti-cyclic citrullinated peptide (CCP) antibodies, IgM rheumatoid factor, circulating immune complexes, proinflammatory cytokines, TH0/TH1 lymphocytes and homocysteine) may be involved in the atherosclerotic disease development specific to CIRD. A modern therapeutic approach should include the early diagnosis of endothelial dysfunction and atherosclerosis, treatment of CIRD, specific medication designed to control atherosclerosis, changes in patient lifestyle and periodic follow-ups. The assessment and diagnosis of traditional and non-traditional CV risk factors, followed by aggressive prevention and therapy, are necessary to achieve efficient control over the inflammation, immunologic and metabolic disorders specific to CIRD.
Keywords: Atherogenesis